Peer Attachment dan Penyesuaian Mahasiswa Baru Fakultas Psikologi di masa Pandemi Covid-19 - Javier, Reavisy; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
Beginning of college new students requires to be able to adjust well. One of factors that can effect the self adjustment to new students is peer attachment. The purpose of this study was determine the relationship between peer attachment and adjustment of new student from SWCU Faculty of Psychology during the pandemic. Subjects who used in this research where new students batch 2021 from SWCU Faculty of Psychology with a total of 161 students, which were determined using the quota sampling technique. This research is used quantitative method, scale who used to measure the peer attachment variable is Inventory of Parent and Peer Attachment (IPPA) by Armsden & Greenberg (1987) and the scale for measure new student adjustment is the Inventory of New College Student Adjustment (INCA) developed by Watson and Lenz (2018). The results showed that there was a significant positive relationship between peer attachment and the adjustment of new SWCU Psychology Faculty students during the pandemic with a value of r = 0.532 with a significance of 0.000 (p < 0.05). So it can be concluded that to improve the adjustment of new students, they also need to build quality peer attachment. Masa awal perkuliahan mahasiswa baru dituntut untuk dapat menyesuaikan diri dengan baik. Salah satu faktor yang mempengaruhi penyesuaian mahasiswa baru adalah peer attachment. Tujuan penelitian ini untuk mengetahui hubungan antara peer attachment dengan penyesuaian mahasiswa baru Fakultas Psikologi UKSW di masa pandemi. Subjek dalam penelitian ini adalah mahasiswa baru angkatan 2021 Fakultas Psikologi UKSW dengan jumlah 161 mahasiswa, yang ditentukan dengan teknik quota sampling. Penelitian ini menggunakan metode kuantitatif, dengan menggunakan skala adaptasi dari Inventory of Parent and Peer Attachment (IPPA) milik Armsden & Greenberg (1987) untuk mengukur variabel peer attachment dan skala untuk mengukur penyesuaian mahasiswa baru menggunakan Inventory of New College Student Adjustment (INCA) yang dikembangkan oleh Watson dan Lenz (2018). Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif signifikan antara peer attachment dengan penyesuaian mahasiswa baru Fakultas Psikologi UKSW di masa pandemi dengan nilai r = 0,532 dengan signifikansi sebesar 0,000 (p < 0,05). Sehingga dapat disimpulkan bahwa untuk meningkatkan penyesuaian mahasiswa baru, mereka juga perlu membangun peer attachment yang berkualitas.